Faktor-Faktor Penyebab Terjadinya Kecelakaan Kerja Pada Karyawan Konstruksi Bangungan Gedung: Studi Literatur Review - Desi Rambe; Susilawati S (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Background: Construction is an activity to build facilities and infrastructure. Construction projects are activities that are prone to accidents at work. Especially in the construction of buildings there are several factors that can cause work accidents. Several factors can cause accidents at work in building construction construction employees, namely human factors, environmental factors and work factors. These four factors themselves are the cause of work accidents in building construction workers. Purpose: This literature review study aims to find out what are the factors that cause work accidents among construction workers in building construction. Research Methods: The research design includes a literature review, namely research that finds theory and analyzes it. The results of this study are the factors that cause work accidents in construction workers, the results show that the most dominating factor is the human factor, followed by environmental factors and work factors.